Keratin fibres derived from tannery industry wastes for flame retarded PLA composites. (June 2017) - Sanchez-Olivares, Guadalupe; Sanchez-Solis, Antonio; Calderas, Fausto; Alongi, Jenny
Abstract: In this work, keratin fibres (KFs) were recovered from tannery industry wastes and reused for preparing completely green materials based on poly(lactic acid) (PLA) composites. A specific process for extracting and treating KFs as reinforcing and flame retardant agents for PLA was used. KFs were characterised by scanning electron microscopy, thermogravimetric analysis (TGA) and total nitrogen content by Kjeldahl method. PLA was compounding using both KFs at different contents and KFs in combination with a traditional flame retardant, namely, aluminium trihydroxide (ATH), in order to exploit the joint action between these two species. PLA composites were studied by scanning electron microscopy, thermogravimetry in nitrogen and air, UL94 classification, dynamical-mechanical, mechanical and rheological measurements. As a result, a good KF/polymer matrix adhesion was observed. Thus, PLA passes from V2 with only KFs (3 phr) to V0 classification when KFs are added in combination with 30 phr ATH. Tensile strength was increased by 16%, strain at break by 40% and tenacity by 66% when ATH content was reduced from 50 phr to 30 phr in joint combination with 3 phr KF content. Rheological measurements in simple and oscillatory shear flows showed that KFs reduced the viscosity of the investigated materials, improving the processability of composites.